The histopathological prevalence of malignant catarrhal fever in swamp buffaloes slaughtered in the private slaughterhouses in Bogor district - Damayanti, Rini (Indonesian Animal Sciences Society, 1995)
Surveys were conducted in five private slaughterhouses in Bogor district to reveal the histopathological prevalence rates of malignant catarrhal fever (MCF) cases in buffaloes . The study was carried out from 1992-1994 in five sub-districts, namely: Ciawi, Caringin, Cijeruk, Megamendung and Cisatua, covering 47 villages . Thirty- two samples (18 .1%) from a total of 177 were histologically being positive for MCF, although the distribution and the severity of lesions were varied amongst them . From those 32 cases examined, lesions observed in the rete mirabile, lung, kidney, liver, urinary bladder, spleen, abomasum, heart, and small intestine were as follows : 84.4%, 77 .3%, 65 .6%, 53 .1%, 28.196, 18 .8%, 9 .4%, 9 .1%, and 3.1% respectively. Keywords : Malignant catarrhal fever, swamp buffalo, prevalence, lession distribution, histopathology